(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the patient’s satisfaction and identify some factors related to patient’s satisfaction with medical examination and treatment services at some medical stations and polyclinics at Soc Son district health center, Hanoi in 2023. Subject and method: A cross-sectional study was conducted on 987 patients from June 2023 to July 2023. Results: The overall satisfaction rate with medical examination and treatment services of 987 patients is 89.9% and there is a relationship between the overall satisfaction rate with gender, education level, travel time, and staff attitudes and medical examination and treatment costs. Conclusion: The patient satisfaction rate with medical examination and treatment services at primary healthcare medical facilities is quite high. However, commune health stations and regional polyclinics need to continue to take measures to improve patients’ access to medical services and organize training classes for medical staffs to improve the quality of medical services, thereby increasing people’s satisfaction when coming for medical examination and treatment.